Health situation of obstetricians in Peru during the COVID-19 pandemic, 2021 - Santos-Rosales, Yuly Raquel (2021)
Introduction: The COVID-19 pandemic has accentuated the deficiencies of the Peruvian health system, affecting the health of obstetricians in the first line. Objective: To analyze the physical, psychological and social health situation of obstetricians in Peru during the COVID-19 pandemic. Materials and Methods: Quantitative, observational, descriptive, cross-sectional study. 511 obstetricians participated by non-probability sampling for convenience. A questionnaire was applied in Google Forms validated by expert judgment and reliable (0.81). The main variables were COVID-19, physical, psychological and social health; secondary variables, general characteristics and exposure to COVID-19. The data were analyzed in SPSS version 26, using descriptive statistics. Approved by the ethics committee of the Faculty of Medicine of the UNMSM. Results: 56.2% of obstetricians were 40 to 59 years old, 41.7% married, 42.8% from Lima, 57% working at the first level of care. 32.5% were screened one to three months before, 3.7% never; being the serological test the most used (42.3%), the prevalence of infection by COVID19 was 42.3%, the most frequent clinical manifestations were headache (32.3%), sore throat (24.9%) and myalgia (23.5%), 73.7% received outpatient management, 1.3% required intensive care. Physical health: The most frequent comorbidities were obesity (20%), hypertension (7.4%) and diabetes (2.7%); 44% performed aerobic exercise at times; 18.2% never; 40% had good diet and sleep habits at times; 1.6% used tobacco and 16.6% alcohol at times. Psychological health: 51.5% manifested depressive symptoms and 48.9% stress several days. Social health: 46.6% have ever felt discriminated against for being a health professional, 6.5% do not have health insurance, 5.5% frequently argued at home. Conclusions: The physical, psychological and social health of obstetricians have been affected in this pandemic, requiring a greater response from the health sector that favors the reduction of risks.